2015
DOI: 10.1111/bju.13360
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thromboembolic disease in men with prostate cancer undergoing androgen deprivation therapy

Abstract: ObjectivesTo investigate the risk of thromboembolic disease (TED) in men with prostate cancer (PCa) on androgen deprivation therapy (ADT), while accounting for known TED risk factors. Materials and MethodsWe assessed TED risk for 42 263 men with PCa who were receiving ADT compared with a matched cohort of 190 930 without PCa. The associations between ADT and deep vein thrombosis (DVT) or pulmonary embolism (PE) were analysed using multivariate Cox proportional hazard regression models, while accounting for pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
3
20
0
2
Order By: Relevance
“…O'Farrell et al assessed the risk of thromboembolic disease in patients with PC undergoing ADT. The group noted that the incidence of deep vein thrombosis and pulmonary embolism increases with prolonged ADT usage and recommended that only men with relevant indication should receive systemic ADT 14. The study also showed an increased thrombotic risk in the patients who switched from antiandrogen therapy to GnRH agonist therapy, although these agonists were not considered in our present analysis 14.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…O'Farrell et al assessed the risk of thromboembolic disease in patients with PC undergoing ADT. The group noted that the incidence of deep vein thrombosis and pulmonary embolism increases with prolonged ADT usage and recommended that only men with relevant indication should receive systemic ADT 14. The study also showed an increased thrombotic risk in the patients who switched from antiandrogen therapy to GnRH agonist therapy, although these agonists were not considered in our present analysis 14.…”
Section: Discussionmentioning
confidence: 68%
“…The group noted that the incidence of deep vein thrombosis and pulmonary embolism increases with prolonged ADT usage and recommended that only men with relevant indication should receive systemic ADT 14. The study also showed an increased thrombotic risk in the patients who switched from antiandrogen therapy to GnRH agonist therapy, although these agonists were not considered in our present analysis 14. Teoh et al 31 observed that ADT users presented an increased risk of ischaemic stroke relative to non-ADT users in patients with PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…anti-androgen treatment), and, as in other medical fields, clinically significant concomitant disease presence [14,[205][206][207][208]. The presence of cancer also increases the risk for symptomatic VTE occurrence after upper urinary tract surgeries up to 1-5% [14,179,12,183].…”
Section: Venous Thromboembolism Prophylaxis In Cancer Patientsmentioning
confidence: 99%
“…GnRH agonists are also associated with metabolic adverse effects including bone loss with increased risk of fractures [5][6][7] , cardiovascular disease [8][9][10][11][12] , stroke 10,11,13 , thrombolytic events 14 , type 2 diabetes 9,15,16 and dementia 17 . For AA, the most frequently reported adverse events are breast pain and gynaecomastia 18 .…”
Section: Introductionmentioning
confidence: 99%